The century of major repairs : Foundation reinforcement and other structural interventions in Amsterdam in the early modern period (Bulletin KNOB, 2023)
This article considers several major repairs to Amsterdam buildings during the seventeenth and eighteenth centuries. It concerns two types of reparation: strengthening of foundations and repair of supporting and roof structures. Foundation problems could be caused by a fluctuating groundwater level, an insufficiently deep foundation, or defects in the construction, sometimes compounded by irregularities in the natural marshy substratum. Apart from houses, whose foundations had already been reinforced much earlier, repairs to towers were undertaken from the early seventeenth century. This usually entailed sinking supplementary footings to which the existing structure was anchored. Well-known examples are the Stadhuis tower, the Montelbaan tower and the tower of the Oude Kerk.Repairs to supporting and roof structures were often due to other issues such as overdue maintenance, overly heavy or incorrect loading, construction defects, and the effect of external forces like wind. Repairs to the roof of the Burgerzaal in 1700 were due to faulty construction and water ingress. An example of external forces was the Lisbon earthquake of 1 November 1755, which was also felt in Amsterdam, and two further tremors in December of that year and on 18 February 1756. It was probably these earthquakes that prompted the city authorities to demolish dilapidated houses shortly hereafter and to carry out major repairs to the Montelbaan tower and the Oosterkerk.As the examples presented in this article show, very costly repairs were sometimes required to ensure a building’s continued existence. But what is also clear is that while some of this restoration work was undertaken in response to a single incident like an earthquake, the phenomenon of restoration is inherent to the long lifespan of buildings.